Near-infrared activatable phthalocyanine-poly-L-glutamic acid conjugate: increased cellular uptake and light-dark toxicity ratio toward an effective photodynamic cancer therapy - Kiew, Lik Voon; Cheah, Hoay Yan; Voon, Siew Hui; Gallon, Elena; Movellan, Julie; Ng, Kia Hui; Alpugan, Serkan (Elsevier Science Bv, 2017)
In photodynamic therapy (PDT), the low absorptivity of photosensitizers in an aqueous environment reduces singlet oxygen generation efficiency and thereby decreases photosensitizing efficacy in biological conditions. To circumvent this problem, we designed a phthalocyanine-poly-L-glutamic acid conjugate (1-PG) made from a new phthalocyanine (Pc 1) monofunctionalized to allow adequate conjugation to PGA. The resulting 1-PG conjugate retained high absorptivity in the near-infrared (NIR) region at its.max 675 nm in an aqueous environment. The 1-PG conjugate demonstrated good singlet oxygen generation efficiency, increased uptake by 4 T1 breast cancer cells via clathrin-mediated endocytosis, and enhanced photocytotoxic efficacy. The conjugate also displayed a high light-dark toxicity ratio, approximately 1.5-fold greater than zinc phthalocyanine at higher concentration (10 mu M), an important feature for the reduction of dark toxicity and unwanted side effects. These results suggest that the 1-PG conjugate could be a useful alternative for deep tissue treatment with enhanced anti-cancer (PDT) efficacy. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: Near-infrared; Poly-L-glutamic acid; Phthalocyanine; Photodynamic therapy; Photosensitizer; Nano-structure